Hpcfolder: a simple tool used to parallelize algorithms using the message passing interface (MPI) - Jani, Kunal; Kumar, Ankit; Nahata, Ronak (The Journal of supercomputing, 2022)
Hpcfolder is a user-friendly high-performance computing tool that can be used to analyze the performance of algorithms parallelized using MPI. It is possible to view the parallel algorithm’s performance in a python notebook file that reads data values from a file and plots graphs by performing calculations on the data values. These plots that are generated by the python script inside the python script in a python notebook are useful in understanding changes in various performance metrics with variation in the number of processes and the problem size. A comparative study was also performed between two simple algorithms which are the multiplication using repeated addition algorithm (which is not computationally intensive) and the matrix multiplication algorithm (which is computationally intensive), and meaningful insights were provided to show the difference in performance of both the algorithms with a variation in the problem size and the number of processors. The goal of this paper is to present how a simple tool can be developed from scratch that can help users analyze the performance of parallel algorithms using MPI.